Effects of physical training and associations between physical performance characteristics and golf performance in female players: a systematic review with meta-analysis - Robinson, L.; Murray, A.; Ehlert, A.; Wells, J.; Jarvis, P.; Turner, A.; Glover, D.; Coughlan, D.; Hembrough, R.; Bishop, C. (The Journal of Strength and Conditioning Research, 2024)
The aims of this systematic review were to assess the association between physical performance and measures of golf performance, and the effects of physical training on measures of golf performance, in female golfers. A systematic literature search was conducted in PubMed, SPORTDiscus, Medline, and CINAHL. Inclusion criteria required studies to (a) have conducted a physical training intervention of any duration in female players and determine the effects on measures of golf performance, (b) determine the association between physical performance in at least one test and golf performance in female players, and (c) be peer-reviewed and published in English language. Methodological quality was assessed using a modified version of the Downs and Black Quality Index tool, and heterogeneity was examined through the Q statistic and I2. Pooled effect sizes were calculated using standardized mean differences (SMDs) (with 95% confidence interval [CI]s) within a random-effects model, with Egger's regression test used to assess small study bias (inclusive of publication bias). Of the 2,378 articles screened, only 9 were included in the final review, with 3 of these being associative by design and 6 being training interventions. From an associative standpoint, clubhead speed (CHS) was reported in all 3 studies and was associated with measures of strength (r = 0.54), lower-body power (r = 0.60), upper-body power (r = 0.56-0.57), and flexibility (r = 0.52-0.71). When assessing the effects of physical training interventions, CHS was again the most commonly reported golf outcome measure (n = 5). The random-effect model indicated that CHS significantly improves within each training group following training interventions (SMD = 0.73 [95% CIs: 0.32-1.14], Z = 3.50, p < 0.001), with trivial heterogeneity (I2 = 0.00%, Q = 0.18; p = 0.9963) and no prevalence of small study bias depicted through the Egger's regression test (z = -0.28, p = 0.78). From the available research, it seems that CHS can be positively affected from strength, power, and flexibility training interventions. From an associative standpoint, only 3 studies have been conducted solely in female players, with one showcasing questionable methodology. Future research should aim to carefully select test measures which better represent the physical capacities needed for the sport when determining the effects of and relationships with golf performance.